Reform on Death Crime in Law Number 1 of 2023 - PRATIWI, I Gusti Agung Istri Ranya Astri; BAGIASTRA, I Nyoman (Indonesia Strategic Sustainability, 2023)
This article aims to analyze, investigate, and understand the reform of the death penalty in Indonesia based on Law Number 1 of 2023, as well as a comparison of the death penalty between China and Indonesia. In this article, the authors use normative legal research methods with a statutory approach. The research results show that the death penalty in Indonesia was initially a primary crime but after the enactment of Law Number 1 of 2023, better known as the New Criminal Code, the death penalty was changed to an alternative crime. This is stated in Article 100 of the New Criminal Code, and convicts have a probation period of 10 years. The sentence can be reduced to life imprisonment if they show commendable morals and behavior. The commendable qualities and behavior are obeying prison regulations and contributing services that benefit the nation and state. Apart from Indonesia, China is a country that still applies the death penalty. Both China and Indonesia have probationary periods before the death penalty is carried out. The probation period is an opportunity for the convict to correct his mistakes. Executions in China are carried out in two ways, namely by being shot in the heart and by lethal injection. In contrast, in Indonesia, they are only shot dead by the executioner.